A home gardening intervention to improve vegetable consumption among urban poor children: A study protocol for randomised controlled trial. Issue 1 (March 2023) - Mok, Kai Ting; Tung, Serene En Hui; Kaur, Satvinder; Chin, Yit Siew; Martini, Mohammad Yusoff; Ulaganathan, Vaidehi
Background: One of the key importance of vegetable consumption is to obtain sufficient micronutrients, dietary fibre, and for the prevention of childhood obesity. Most Malaysian children did not meet the recommended intake of vegetable consumption, and this is especially vulnerable among the urban poor population due to food insecurity. Efforts are needed to promote vegetable consumption that fall short of the recommended intake level.Aim: This trial aims to examine the effectiveness of the "GrowEat" project, as a nutrition intervention programme integrated with home gardening activities to improve vegetable consumption among urban poor children in Kuala Lumpur, Malaysia.Methods: This is a single-blinded parallel two-arm cluster randomised controlled trial (RCT) that include 134 children. Two zones in Kuala Lumpur will be randomly selected, and three low-cost housing flats from each zone will be selected as the intervention and control groups respectively. The trial is designed based on the social cognitive theory (SCT). Children from the intervention group ( n = 67) will attend a 12-week programme, which consists of home garden-based activities, gardening and nutrition education session. Assessment will be conducted for both groups at three time points: baseline, post-intervention and follow-up phase at 3 months after the intervention.Conclusion: We anticipate positive changes in vegetable consumption and its related factors after the implementation of the "GrowEat" project. The current intervention may also serve as a model and can be extended to other urban poor population for similar interventions in the future to improve vegetable consumption, agriculture and nutrition awareness.